Two cases of viper bite: still an important health problem - Hajra, Adrija; Bandyopadhyay, Dhrubajyoti (International Journal of Research in Medical Sciences, 2016)
Viper venoms act mainly as hemotoxic. Manifestations of snakebites depend on specific toxins that constitute the venom. The local and systemic snake bite related symptoms are directly linked to the toxicity of the venom. Edema, ecchymoses, hematoma, and gangrenous lesions are reported to occur as local symptoms. Systemic symptoms may include fever, nausea, vomiting, delirium, jaundice, circulatory collapse, convulsions, and coma. Death from secondary infections, neurotoxicity, disseminated intravascular coagulation (DIC), intracranial hemorrhage, and acute renal failure are the well-known facts. For reduction of morbidity and mortality, it is important that antiserum is administered at the appropriate dose as early as possible after snake bite. There are several case reports about various complications of viperid bite. Here we are discussing two cases of viper bite. These cases are unique because of the extensive tissue necrosis. One of them succumbed to septicemia after acute pancreatitis.